Power converters for the grid integration of PV systems - Shau, Wei Leong. (2013)
In most applications of grid-connected PV systems, buck converter is usually used with Maximum Power Point Tracker (MPPT) controller to achieve maximum power transfer by controlling the duty ratio of its switch. However, it is important for buck converter to operate in continuous conduction mode (CCM) because it makes the control and regulation of the output voltage easy. It can be shown that by varying the inductance value of the inductor in the buck converter, one can control the operation to be in continuous or discontinuous region. So far, there has been some research going on for variable inductor to achieve maximum power point tracking, and using magnetic control to change the inductance in the variable inductor.